MANAJEMEN PEMBELAJARAN BERBASIS E-LEARNING HUBUNGANNYA DENGAN EFEKTIVITAS PEMBELAJARAN - Indah Lestari; Aep Tata Suryana; A Heris Hermawan (Jurnal Isema : Islamic Educational Management, 2022)
This research is based on the existence of e-learning management that offers less solutions to the problems of the education world, causing learning to decline in the effectiveness of the pandemic.The problem is reflected in the madrasah aliyah city of bogor, which performs study based e-learning with an application e-learning madrasah and experiences a decline in learning effectiveness, such as the lack of interaction impact, the educators who do not empower the opticible e-learning system and other infrastructure management barriers. The purpose of this research is specifically to discuss the reality of the relation between learning management and learning effectiveness in state Madrasah Aliyah throughout the city of Bogor with quantitative research type descriptive method and using random samples with the slovin formula a significance level of 10% so that the number of research samples is 100 madrasah students. The results showed that there was a relationship between e-learning based management and learning effectiveness in Madrasah Aliyah Negeri of Bogor City with a significance level of 0.604** included in the correlation coefficient value of 0.60-0.799, meaning that the relationship between the two variables was included in the strong significant category. so that if e-learning-based management is improved, the effectiveness of learning will also increase.